Pengembangan Aplikasi Skrining dan Pemantauan Risiko Preeklamsi Awitan Dini Berbasis Android untuk Ibu Hamil di Layanan Primer - Pangesti, Wilis Dwi; Fauzan, Achmad; Syahdony, Farrel Nolan; Riani, Evicenna Naftuchah; Pratiwi, Erlina Lutfiayu; Suri, Mulhamatus Latifatus; Setiawati, Elsa Pudji; Pribadi, Adhi; Hilmanto, Dany (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Early onset preeclampsia is a hypertensive condition during pregnancy that has a significant impact on maternal morbidity and mortality rates globally. The incidence of preeclampsia with complications in Indonesia is 14%, which is higher than the general incidence of preeclampsia. This serious condition can be a threat to the lives of the mother and fetus if not prevented. One effort to reduce the incidence of early onset preeclampsia is to take preventive measures by identifying risk factors from the start. The application of technology to education in the health sector has been widely developed. Android-based applications make it easier for users to gain knowledge about the risk factors for pregnancy, one of which is early onset preeclampsia. Early onset preeclampsia can be predicted by screening for risk factors at less than 20 weeks of gestation. The activeness of pregnant women in Understanding the risk of early onset preeclampsia plays an important role in reducing the incidence of preeclampsia complications in pregnancy. The development of an application for the screening and monitoring of early onset preeclampsia aims to make it easier for pregnant women to independently screen and monitor pregnancy. The resulting features included risk factor screening, health worker consultation, and early onset preeclampsia education. A Likert scale was used to assess the material in the application by three material expert validators. The results of the total validation of material experts obtained highly feasible results (92.22%) to be tested on users with several improvements.